O Ministério Presbiteral na reflexão da Igreja do Brasil : uma análise da recepção do Concílio Vaticano II e uma proposta teológica a partir dos Encontros Nacionais de Presbíteros - Vian, Ludinei Marcos (2020)
The present thesis aims to synthetize analytically the National Presbytery Meetings and to propose, from a trinitarian rationale of the presbyterial identity, a path in which the missionary trinitarian identity for the Brazilian presbyters can be constructed. In order to achieve such goals, the present thesis uses as criteria the Second Vatican Council and what developed after this event, not only by the church’s magisterium, but also by theology. The methodology used is an analytical annotated bibliography which has on its center the documents available in each National Presbytery Meeting. The relevance of such theme is the finding of the importance the presbyter has in Church’s life, and in Brazil and its responsibility when it comes to encouraging the community, together with the presbyter and the diocesan bishop, the community’s pastoral, missionary, and administrative activities. The conclusions are the National Presbytery Meetings have a fundamental role for the articulation of Brazilian presbyters; they are in a process of reception of the Second Vatican Council; the main themes approached on the encounters have a pastoral focus; there is the necessity of continuing deepening and reflection about the presbyter ministry integrating to the meetings the proprium of the presbyterial identity, which is the trinitarian rationale.